Debt Shifting and Transfer Pricing in a Volatile World - Nicola Comincioli; Paolo Panteghini; Sergio Vergalli (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In this article we introduce a stochastic model with a multinational company (MNC) that exploits tax avoidance practices. We focus on both transfer pricing (TP) and debt shifting (DS) activities and show how their optimal level is chosen by the shareholders. In addition, we perform an extensive numerical simulation, fine-tuned on empirical data, to measure the impact of tax avoidance practices on the MNC's value and to study their sensitivity to exogenous variables. We will show that: an increase in risk sharply reduces leverage and slightly decreases a MNC's value; the cost of TP leads to a sharp reduction in the MNC's value, whereas it does not affect leverage; the impact on MNC's decisions is increasing in the tax rate differential; finally, the cost of DS has always a relevant impact on both MNC's value and leverage.
Keywords: H25; G33; G38; 330; capital structure; default risk; business taxation and welfare